2008
DOI: 10.1086/588020
|View full text |Cite
|
Sign up to set email alerts
|

Polar Plume Brightening During the 2006 March 29 Total Eclipse

Abstract: We discuss a remarkable brightening in a polar plume, as inferred from unique coordinated observations of the whitelight corona during the total eclipse of the Sun of 2006 March 29. The polar plume (also known as a polar ray, with distinctions that we discuss) was observed at the positional angle of 9 ; the velocity at which the brightening propagated was about 65 km s À1 , which is close to the values derived by modeling of mass/energy transfer in polar plumes/rays as well as to those acquired from images fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…However, we sampled only one active region for one instant, so our results are not inconsistent with reports of higher velocities [19]. We note that, during the 2006 eclipse, Pasachoff et al [20] found a coronal plume that showed motion at 65 km s −1 .…”
Section: Discussionsupporting
confidence: 51%
“…However, we sampled only one active region for one instant, so our results are not inconsistent with reports of higher velocities [19]. We note that, during the 2006 eclipse, Pasachoff et al [20] found a coronal plume that showed motion at 65 km s −1 .…”
Section: Discussionsupporting
confidence: 51%
“…The nature of the phenomenon they track is not clear: plasma motions or outward propagating waves possibly accounting for the observed behavior. Analogously, Bělík et al (2013) Pasachoff et al (2008): outward propagating brightenings have been detected with speeds in the range 32 -146 km s -1 , whose nature, however, is not clear.…”
Section: Introductionmentioning
confidence: 58%
“…As seen in one location, eclipses are too short to provide valuable information on the plume dynamics, but coordinated observations along the path of eclipse may result in a long enough data set: Pasachoff et al (2008) have been able to follow the propagation of a brightening within a plume over 1:09 hour at the 2006 March 29 eclipse. Tracking the positions of the brightest spot within a plume at different times, these authors give a mean outward speed on the order of 59 -74 km s -1 , over the height interval from the solar limb to ≈ 1.22 ⊙ .…”
Section: Introductionmentioning
confidence: 99%
“…We need the index that characterizes the shape of the corona of the minimal type and is applicable to images and drawings of different qualities. The corona of the solar minimum is characterized by pronounced polar ray structures and large coronal streamers (Pasachoff et al, 2008). Let us introduce the parameter that characterizes the angle between high-latitude boundaries of the large coronal streamers at a distance of 2·R ʘ .…”
Section: Processing Methods and Resultsmentioning
confidence: 99%